Burundi : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report ;, 2021)
Burundi is a fragile state with a history of political tensions and weak institutions. Before the Covid-19 pandemic, Burundi was recovering from an economic recession triggered by the 2015 political crisis stemming from the late President Nkurunziza's decision to run for a third term. Real GDP growth was positive, at 1.8 percent in 2019, but difficult policy challenges persisted.